Accuracy of publicly-listed locator information for buprenorphine waivered practitioners and opioid treatment programs in the US, 2020. Issue 1 (1st December 2022) - Barenie, Rachel E.; Winbigler, Brian L.; Heidel, R. Eric; Wheeler, James S.
Abstract: Background: Opioid use disorder affects millions of Americans, but only a fraction receive treatment. This may be due in part to inaccurate information available about buprenorphine waivered practitioners (waivered practitioners) and Opioid Treatment Programs (OTPs) on public, federally-sponsored locator databases. We aimed to assess the accuracy of publicly-listed locator information for waivered practitioners and OTPs across the US. Methods: Using a cross-sectional study design, we randomly sampled waivered practitioners ( n  = 253; 0.5%) and licensed OTPs ( n  = 165; 10%) that were publicly-listed on a federally-sponsored database. We used a three-pronged approach to assess the accuracy of the information available by concurrently administering a phone survey (making up to 3 attempts to contact), conducting online searches, and reviewing provider information on state board websites (practitioners only) between August and November 2020. We used descriptive analyses and inferential statitistics to analyze the data. Results: Among n  = 418 waivered practitioners and OTPs sampled, many were located in the South and in an urban area. For the phone survey, researchers were able to reach OTPs nearly twice as often as waivered practitioners. Of those reached, n  = 19 waivered practitioners and n  = 40 OTPs agreed to participate, and we found most had up-to-date contact information. OTPs yielded significantly more online search results and matching contact information than waivered practitioners ( p  < 0.001). Most waivered practitioners were located on state licensing board websites, but few had contact information listed, and only one listed the practitioner's waiver status. Conclusions: Waivered practitioners and OTPs were difficult to reach via phone but easier to find online and on state licensing board websites; when they were reached via phone, their contact information was very accurate. Whether challenges locating a waivered practitioner or OTP is associated with lower treatment utilization should be evaluated.